Investigation of structural and optoelectronic properties of n-MoS2/p-Si sandwiched heterojunction photodetector - Ahmad, Harith; Rashid, Haroon; Ismail, Mohammad Faizal (Elsevier, 2019)
Molybdenum disulphide (MoS2), a member of the transition metal dichalcogenides family has shown excellent optoelectronic properties with direct or indirect bandgaps in visible range as well as good absorption in its 2-dimensional (2D) form. In this work, a polycrystalline MoS2 thin film is fabricated by radio frequency magnetron sputtering. X-ray diffraction (XRD) analysis of the fabricated sample reveals two hexagonal structured peaks along the (100) and (110) planes, while energy-dispersive X-ray (EDX) spectroscopy confirms a non-stoichiometric MoS2 film with a thickness of 300 nm. Raman shifts are observed at the E1 2g and A1g phonon modes, located at 374.37 cm−1 and 407.75 cm−1 respectively. A sandwiched heterojunction photodetector with a SLG/n-MoS2/p-Si structure is fabricated and illuminated with violet light at 441 nm. The device exhibits significant optoelectronic properties at various laser powers at a 10 V bias voltage. The maximum value of the photocurrent is calculated as 0.79 μA, with the responsivity as 10.4 mAW−1 and detectivity of 6.74 × 109 Jones at an intensity of 0.004 mW/cm2. These results highlight the adaptability of the current technique that will help realize large-scale production as well as allow for the development of advanced optoelectronic devices. © 2019 Elsevier GmbH